2019
DOI: 10.1371/journal.pone.0218111
|View full text |Cite
|
Sign up to set email alerts
|

Gene-based analysis in HRC imputed genome wide association data identifies three novel genes for Alzheimer’s disease

Abstract: Late onset Alzheimer’s disease is the most common form of dementia for which about 30 susceptibility loci have been reported. The aim of the current study is to identify novel genes associated with Alzheimer’s disease using the largest up-to-date reference single nucleotide polymorphism (SNP) panel, the most accurate imputation software and a novel gene-based analysis approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Building upon IGAP (2013) 26 dataset, single nucleotide 26,[30][31][32][33][34] , gene-wide 35,36 , transethnic 32 and proxy design 31,37,38 (based on reports of parental history) studies have identified numerous novel genome-wide significant (GWS) loci, see Table 1 and Figure 1.…”
Section: Late-onset Ad Genetics: Common Variationmentioning
confidence: 99%
“…Building upon IGAP (2013) 26 dataset, single nucleotide 26,[30][31][32][33][34] , gene-wide 35,36 , transethnic 32 and proxy design 31,37,38 (based on reports of parental history) studies have identified numerous novel genome-wide significant (GWS) loci, see Table 1 and Figure 1.…”
Section: Late-onset Ad Genetics: Common Variationmentioning
confidence: 99%
“…To illustrate this, we use AD as an example. For AD the R 2 is 0.16 for APOE alone and 0.1 for the PRS excluding APOE locus (in house analysis in GERAD data ( Baker et al, 2019 ) using summary statistics from ( Kunkle et al, 2019 )). AUC is the accuracy of the prediction, comparing the observed case/control status and the predicted classification estimated by a logistic regression model.…”
Section: Risk Prediction In Neurodegeneration With Polygenic Risk Scomentioning
confidence: 99%
“…This success can be largely attributed to the extensive collaboration across four genetic consortia; Genetic and Environmental Risk in AD (GERAD), European AD Initiative (EADI), Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) and AD Genetics Consortium (ADGC), badged together as the International Genomics of Alzheimer's Project (IGAP). In addition, genome-wide gene-wide analyses identified five novel genome-wide significant loci, TP53INP1, IGHV1-67, [17] PPARGC1A, RORA and ZNF423 [18] using the IGAP dataset. Building upon the initial IGAP dataset, TRIP4 [19], ECHDC3 [7,20], IQCK, ACE, ADAM10 and ADAMTS1 [7] have more recently been reported as genome-wide susceptibility loci.…”
Section: Identified Common Risk Locimentioning
confidence: 99%